Economic Instrument Approach Related to the Giving of Environmental Insurance in the Enforcement of Environmental Law - Muh. Hasrul, Iin Karita Sakharina, Sukri Palutturi, Ratnawati, Andi Tenri Famauri, Syafa’at Anugrah Pradana (International Journal of Advanced Science and Technology, 2020)
Related to economic instrument approach of environmental insurance gift specially in enforcing the environmental law intrinsically, it has been regulated in Law number 32 of 2009 on the environmental protection and management in the article 42 paragraph 1 affirming that in order to preserve the environment function, the central government and the local government are obliged to expand and apply the environmental economic instrument. One of them is environmental insurance development. The reality of environmental insurance is the incurrence of giving protection when the environmental contamination or damage occurs. The purpose of this study was to examine the position and function of environmental insurance in environmental law enforcement and the extent of the impact caused by the provision of environmental insurance through an economic instrument approach to environmental law enforcement. This research used literature review. This study found that environmental insurance is basically similar to conventional insurance, only that the object of insurance is a more common property and open access (not private). The claim calculation approach is more comprehensive and requires a special approach. Environmental insurance can function as a means of overcoming environmental pollution, because environmental insurance is one way to guarantee the cost of environmental recovery in the event of pollution or damage. Environmental insurance provides many benefits for businessmen as well as other parties and also for environmental preservation. Environmental insurance is very important in providing protection and guarantee to the community to be able to continuously obtain ecological and economic benefits from the natural resources and the environment that is in the vicinity. This paper proposes suggestions, including the permits granted by the local governments should be re-evaluated, then the government should be more objective and selective in granting licenses to mining companies today.